Framing Media Kebijakan Pajak Karbon: Implikasinya Terhadap Kepatuhan Perusahaan di Sektor Energi Indonesia - Dea Arme Tiara; Dania Meida Rosyidah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes how the media frame carbon tax policies and their implications for corporate compliance in Indonesia’s energy sector, using Entman’s framing framework, which includes problem definition, causal interpretation, moral evaluation, and treatment recommendation. The analysis reveals that the media more frequently define issues related to the carbon tax from environmental and energy perspectives (18 coverages) compared to other aspects such as economic, social, or political dimensions (12 coverages). The emphasis on environmental aspects reflects the media’s effort to shape public opinion that the carbon tax is an essential instrument for climate change mitigation, while other issue framings are positioned as supporting factors. These findings indicate that media framing has the potential to influence business actors’ perceptions and attitudes, particularly regarding the urgency of policy implementation. With the dominance of environmental framing, the media can foster a narrative of corporate responsibility for sustainability, although challenges remain in delivering a balanced message between sustainability and economic burdens. This study recommends the adoption of a more comprehensive framing approach so that the carbon tax policy can be understood holistically, thereby encouraging higher levels of corporate compliance.